(3QSGdI aj JbOje GdahGcg Ydi GdCWYeIs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3GNJda GdCWHGA ai JbOje GdahGcg bHd GdWYGe hGdCWYeI bHd GdahGcg abGd aQbI jfHZi Cf JbOe GdaGcgI bHd GdWYGe hge GdMd hGdLeghQ s
(3BNQgG (B:s
(3hCeG GdJjf acCfgG ef GdSaQLd hEf cGf gi TF ef gPg de Jbd ajg abO jecf ef YQa bhGgG GSJNQGL eG jMJGL Edjg ef Pdc Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs